Promoting Civic Engagement of Youth through New Media and Information Literacy - Muhammad Majid Hamid Nasir,; Dr. Saqib Riaz, (Al-Qanṭara, 2024)
The rapid rise of New Media has enabled society to share information through Information and Communication Technology (ICT). It has become a vital tool for information dissemination, leading to the emergence of a Media Literate. New Media has also evolved into a platform for sharing civic knowledge, addressing social issues, and engaging in civic activities, commonly known as "Civic Engagement." Young people, in particular, have been instrumental in leveraging platforms like Facebook, Twitter, YouTube, and Instagram for Civic Engagement. For this, a survey of 450 university students in Punjab, Pakistan, was conducted. The results indicate that these students actively use New Media for various Civic Engagement activities, including fundraising, political involvement, advocacy campaigns, and social innovations. The empirical evidence suggests a strong correlation between increased use of New Media platforms for Civic Engagement by university students and a subsequent increase in Civic Engagement across society as a whole.